The Role of School Activities Program in Supporting the Culture of Entrepreneurship among students of the tenth and eleventh grades in the Governorate of South Al Batinah in (Oman) - Al-Zadjali, Mohammed Malallah; Al-Hataali, Mohammed Suleiman (Journal of Educational and Psychological Sciences, 2022)
The study aims to identify the level of awareness of the culture of entrepreneurship among students of the tenth and eleventh grades in the schools of the Governorate of South Al Batinah in the Sultanate of Oman, as well as the role of school activities in supporting that culture. A questionnaire consisting of 20 items was used to measure awareness and effectiveness, and its validity and reliability were measured. It was applied to a sample of 848 male and female students in the second semester of the academic year 2019/2020. The results showed that the level of awareness of the culture of entrepreneurship was medium, and that the level of effectiveness of school activities in supporting the culture of entrepreneurship was low, and that there were differences in the variables of awareness and effectiveness due to the variables of gender and participation in school activities, and that there were no differences due to the variable of class. The study sample presented proposals to support entrepreneurship activities in schools, the most important of which are: The necessity of having specialists in entrepreneurship in schools. The study recommended the need to enhance the role of school activities in supporting the culture of entrepreneurship in schools.